Calidad fisicoquímica de lactosa anhidra materia prima de un laboratorio farmacéutico nacional - Esquivel Chuquimango, José Javier (2019)
In the present report, the evaluation of the physicochemical quality of three batches of anhydrous lactose raw material of a national pharmaceutical laboratory was carried out through physicochemical parameters such as: description of the sample, solubility and identification by infrared spectrophotometry, identification by thin-layer chromatography, specific tests such as the determination of water by Karl Fischer, transparency and color of the solution, optical rotation, acidity or alkalinity, loss on drying, residue of incineration, proteins and impurities that absorb light; which were based on the analytical technique of the laboratory, taking as a reference the Pharmacopoeia of the United States (USP 40). The results for each analysis were consistent, and within the physicochemical parameters met the specifications established in the analysis protocol of the quality control department for anhydrous lactose as raw material